Impact of the University Business Consulting Office on Entrepreneurial Learning: A Bayesian Approach - Guerrero, Lugo Manuel Barbosa; Rozo, Jairo Jamith Palacios (Journal of Ecohumanism, 2024)
The University Business Consulting Office has established itself as a support strategy for Colombian micro-entrepreneurs, promoting entrepreneurial learning and the sustainability of their businesses. This study aims to analyze the perception of learning acquired by micro-entrepreneurs who have participated in training activities within the framework of this consulting office. To this end, a quantitative approach with Bayesian methodology was used, employing the binomial test to classify the responses of 327 entrepreneurs from 16 Social Intervention Centers (CIS) in Bogotá. The results show that 53.8% of the participants expressed being completely in agreement with having acquired significant knowledge in their entrepreneurship, while 27.8% indicated being in agreement. The binary classification analysis also reveals high accuracy in detecting positive perceptions about learning, with a sensitivity and specificity of 80.1%. Additionally, a positive predictive value of 31.5% was identified, suggesting that entrepreneurs who report having learned effectively are the majority. These findings highlight the positive impact of the University Business Consulting Office in strengthening entrepreneurial competencies, promoting business development through continuous training. Finally, future research is suggested to include regional comparisons and longitudinal analyses to assess the sustainability of learning over time.